Pemberdayaan masyarakat miskin di pedesaan dalam rangka ‘Making Pregnancy Safer' studi dan implikasi terhadap upaya pelayanan kesehatan maternal - Ristrini Siswanto (Berita Kedokteran Masyarakat (BKM), 2005)
Background: The objective of this study was to analyze the situation of the empowerment of poor community for making pregnancy safer (MPS) in rural areas including the empowerment of health efforts and fund mobilization and transportation aid to refer deliveries. Method: It was a descriptive explorative study held in three districts, i.e. Kupang, Timor Tengah Selatan (TTS) in Nusa Tenggara Timur, and Ponorogo in East Java. In each district, two poor sub districts were chosen and in each sub district, ten poor villages were chosen. The analysis unit in this study was village. The data were gathered with in-depth interview, structured interview, secondary data, and Focus Group Discussion (FGD), and were analyzed descriptively. Result and Conclusion: The result shows that the empowerment of traditional birth attendants' activities, integrated health service post activities, village delivery house activities, and cadre activities performed by the community varied. The empowerment for village medicine post activities was relatively low. The empowerment of the community in fund mobilization on maternal health was hard to do due to the implementation of social safety net on health sector (JPSBK) fund as well as PKPS BBM on health sector. The empowerment to providing transportation in villages seems to invoke minimum responses. Keywords: empowerment, making pregnancy safer, traditional birth attendance integrated services post, village delivery house